Towards the development of a common starter culture for fufu and usi (edible starch): Screening for potential starters - Kubrat A. Oyinlola; Anthony A. Onilude; Oluwaseun E. Garuba (International Journal of Food Studies)
Fermented cassava products like fufu and usi are important staple foods in many African homes. Natural fermentation time is usually long resulting in slower acidification and inconsistent nutritional composition of products which could be overcome with the use of starter culture. However, most available starters are used for single food fermentation and are uneconomical. This necessitates the development of a starter culture for multiple related food products to reduce cost. Hence, this study aimed at screening for potential starters in the development of a common starter culture for fufu and usi. Fresh, peeled, chipped and grated cassava tubers were spontaneously fermented and lactic acid bacteria were isolated from the fermenting mash at 24 hour intervals. Ninety eight (98) isolates were randomly picked. Lactobacillus plantarum had highest occurrence (50.0%) in both fermentations. All selected isolates did not hydrolyze starch, but produced linamarase and pectinase. Fermenting pH ranged between 6.50 and 3.58 during 72 hours fermentation. Lactic acid concentration ranged from1.10 g/L to 1.78 g/L at 24 hours, 1.22 g/L to 2.45 g/L at 48 hours and 0.57 g/L to 2.55 g/l at 72 hours. The highest hydrogen peroxide concentration produced was 629 µg/L at 24 hours while the least was 136 µg/L at 72 hours. 1.08 g/L of diacetyl was the least concentration produced at 24 hours while the highest was 2.86 g/L at 48 hours. Five potential starters were identified as Lactobacillus pentosus F2A, L. plantarum subsp. argentolarensis F2B, L. plantarum F2C, L. plantarum U2A and L. paraplantarum U2C.